Effect of apelin on cardiac contractility in acute reno-vascular hypertension: The role of apelin receptor and kappa opioid receptor heterodimerization - Mahboobeh Yeganeh-Hajahmadi; Hamid Najafipour; Farzaneh Rostamzadeh; saeed Esmaeili Mahani; Siavash Joukar (Iranian Journal of Basic Medical Sciences, 2018)
Objective(s): Apelin/APJ system plays an important role in the regulation of myocardial contractility (MC) and blood pressure. Opioid receptors (OPRs) are also important cardiovascular regulators and exert many of their effects through modulating the function of other systems. This study analyzed the interaction between APJ and kappa OPRs (KOR) in cardiac responsiveness to apelin in acute reno-vascular hypertension (2K1C).Materials and Methods: MC studies were carried out on 2K1C rats. F13A (APJ blocker), Naloxone (OPR inhibitor), nor-Binaltorphiminedihydrochloride (nor-BNI; kappa OPR inhibitor), PTX (Gi path inhibitor) and chelerytrine (protein kinase C; PKC inhibitor) were administered prior to apelin 20 and 40 μg/kg. The phosphorylation of extracellular signal–regulated kinases (ERK1/2) (PERK) was also assessed. Dimerization of APJ and KOR was evaluated by immunoprecipitation.Results: Both doses of apelin reduced blood pressure. Apelin 40 exerted a negative inotropic effect, which was inhibited by nor-BNI, but apelin 20 showed a positive inotropic effect, which was resistant to this inhibition. Hypertension increased heterodimerization of the APJ and KOR and this was reduced by apelin 20. F13A, naloxone and PTX significantly reduced PERK in apelin 40 group, but F13A, naloxone, and chelerytrine significantly increased PERK in the apelin 20 group.Conclusion: The lowering effect of apelin 40 on MC and its non-effectiveness on APJ/KOR dimerization, while augmenting the contractility and reducing the dimerization by apelin 20 implies the APJ/KOR-related effects of apelin on the MC under acute reno-vascular hypertension. This may have potential clinical applications as apelin has been introduced as a potential therapeutic agent in heart failure and opioids are being currently used in the treatment of myocardial infarction.